2022
DOI: 10.1111/pirs.12679
|View full text |Cite
|
Sign up to set email alerts
|

Mapping regional strengths in a key enabling technology: The distribution of Internet of Things competences across European regions

Abstract: The Internet of Things (IoT) can trigger innovation processes across all sectors of the economy. However, this potential is not available to all regions. As with other enabling technologies, the competences required to develop IoT solutions are numerous and varied, ranging from hardware to software and related services, and are often provided by different companies. To map the application potential of these technologies across European regions, we use textual analysis to identify the NACE codes associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…To get on the path of development, a critical mass is needed, as emerging new technological solutions must find an audience that can implement them. The same applies to the IoT and other enabling technologies (Russo et al , 2022). The authors argue that the competence base of regions, particularly the mix of competencies in the IoT, is a critical factor in developing their technological bases in emerging digital technologies.…”
Section: Literature Review On Possible Clusters’ Impact On Industry 40mentioning
confidence: 96%
See 1 more Smart Citation
“…To get on the path of development, a critical mass is needed, as emerging new technological solutions must find an audience that can implement them. The same applies to the IoT and other enabling technologies (Russo et al , 2022). The authors argue that the competence base of regions, particularly the mix of competencies in the IoT, is a critical factor in developing their technological bases in emerging digital technologies.…”
Section: Literature Review On Possible Clusters’ Impact On Industry 40mentioning
confidence: 96%
“…To get on the path of development, a critical mass is needed, as emerging new technological solutions must find an audience that can implement them. The same applies Changing market needs and increasing pressure for innovation; geographical proximity and interaction with other companies and external agents; micro-geographic proximity for the formation of knowledge transfer relationships and different types of inter-organisational relationships: importance of the "neighbourhood effect" to the IoT and other enabling technologies (Russo et al, 2022). The authors argue that the competence base of regions, particularly the mix of competencies in the IoT, is a critical factor in developing their technological bases in emerging digital technologies.…”
Section: Literature Review On Possible Clusters' Impact On Industry 40mentioning
confidence: 99%
“…For example, product-service systems, refurbishment, and the sharing economy are not included in the NACE codes and therefore, companies that employ servitization have to choose the most relevant code for their activities, which will not reflect circularity. Other authors in different research fields found similar problems, for example Russo et al (2022) acknowledge that the Internet of Things are not sufficiently captured by NACE codes, as well as activities related to renewable energy or sustainability (Battiston et al, 2022). Also, a company may choose the correct activity, but might offer both linear and circular activities within this activity.…”
Section: Tablementioning
confidence: 99%
“…We study multiple cases (Yin, 2009), using contextualised explanations and cross-case comparisons to build a model explaining the conditions that allow PIIs to adapt their business models to support the process of upgrading technological systems for digital transition. We conducted four case studies in France and the United Kingdom (UK), two leading European countries with regard to IoT technologies (Russo et al, 2021), using a combination of in-depth interviews with PIIs' internal and external stakeholders (PII staff, firms that work closely with PIIs, policymakers working in agencies funding and evaluating PIIs, academics and consultantsexperts on innovation and IoT) and secondary sources.…”
Section: Introductionmentioning
confidence: 99%